'By the charitie of good people': poverty and neighbourly support in seventeenth century Lancashire. (2nd July 2016) - Healey, Jonathan
Abstract : Historians of early-modern poverty have emphasized the ways in which the poor 'made shift', reducing or even preventing their dependence on formal poor relief. This article looks at one aspect of that 'economy of makeshifts': the casual support of the poor by their neighbours. It uses evidence from a uniquely extensive archive of pauper petitions from Lancashire (1626–1710), many of which contain incidental information about strategies of making shift. The petitions suggest that neighbourly support for the needy was common in Lancashire, both through localized begging and in more stable supportive relationships. Nonetheless, the charity of neighbours could easily be exhausted, leaving those in poverty forced to call upon the more formalized support of the Poor Law.